Thermolysis of octa (hydridodimethylsiloxyl) octasilsesquioxane in pyridine media and subsequent toluidine blue O adsorption - do Carmo, D. R.; Guinesi, L. S.; Dias, N. L.; Stradiotto, N. R. (Elsevier B.V., 2004)
This work describes the synthesis of octa (hydridodimethylsiloxyl) octasilsesquioxane, (Q(8)M(8)(H)) and its thermolysis in pyridine media. The new compound called CPy was characterized by FTIR, NMR-MAS, XRD, MEV spectroscopies and TGA analyses. These results indicate that silsesquioxanes cages (octanion) are maintained after thermal treatment. A cleavage of vertex siloxy groups yielding a nanocomposite with polymeric nature is proposed. Its structure and morphology allows the adsorption/inclusion of electrochemical mediator, toluidine blue O. The square wave voltammetry analysis of resulting composite (CPyTBO) exhibits two redox couple with a formal potential (E-0') 0.1 V and 0.26 V to I and II redox couples respectively, (Britton-Robinson (BR) buffer pH 3, v = 10 Hz versus SCE) ascribed to a monomer and dimmer of the toluidine blue species. This paper opens the use of spherosiloxane derived materials a's host for small molecules in the electrochemical field. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: silsesquioxane; spherosilicate; toluidine blue O; adsorption; electrochemistry